Analysis Of Inpatient Service Development Strategies At Al Irsyad Hospital Surabaya Using Swot Analysis - Flora Fidelia; Pipit Festi; Rachmad Cahyadi (Global Journal of Health Administration, 2026)
Abstract Background : Increasingly fierce competition in the healthcare sector requires hospitals to adopt effective development strategies to improve service quality and competitiveness. The inpatient unit is one of the key services contributing to a hospital’s performance; therefore, regular strategic analysis is necessary. Aims : To analyse the strategic position of the inpatient services at Al Irsyad Hospital in Surabaya using the SWOT method and to formulate a development strategy. Methods : A cross-sectional quantitative analysis utilising secondary data from L  Hospital personnel and attendance records. All 39 structural officials who are currently in office were included in the total sampling. Spearman correlation, the Mann-Whitney U test (X3), and multiple linear regression with log(Y+1) transformation were used to analyse the data in order to address the dependent variable's non-normality. Results : An IFAS score of 3.20 and an EFAS score of 3.10 indicate internal and external conditions that support the development of services. The SWOT analysis yielded coordinates (1.80; 1.50), placing the inpatient service in Quadrant I. This position indicates that the hospital possesses significant internal strengths and high external opportunities. Conclusion : The recommended strategy is an aggressive strategy (SO), encompassing improvements in service quality, the development of flagship services, the optimisation of digitalisation, the enhancement of staff competencies, and the modernisation of healthcare facilities to improve service quality and the hospital’s competitiveness. Keywords : SWOT, IFAS, EFAS, Development Strategies, Inpatient Care.   Abstrak Latar Belakang : Persaingan layanan kesehatan yang semakin ketat menuntut rumah sakit untuk memiliki strategi pengembangan yang tepat guna meningkatkan mutu pelayanan dan daya saing. Unit rawat inap merupakan salah satu layanan utama yang berkontribusi terhadap kinerja rumah sakit sehingga perlu dilakukan analisis strategis secara berkala Tujuan : Menganalisis posisi strategis pelayanan rawat inap Rumah Sakit Al Irsyad Surabaya menggunakan metode SWOT dan merumuskan strategi pengembangannya. Metode : Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus. Sebanyak 50 responden yang terdiri atas manajemen rumah sakit, dokter spesialis, perawat, pasien rawat inap, dan keluarga pasien dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui wawancara mendalam, observasi, dokumentasi, dan Focus Group Discussion (FGD). Analisis dilakukan menggunakan matriks IFAS dan EFAS. Hasil : Skor IFAS sebesar 3,20 dan EFAS sebesar 3,10 menunjukkan kondisi internal dan eksternal yang mendukung pengembangan pelayanan. Perhitungan SWOT menghasilkan koordinat (1,80; 1,50) yang menempatkan pelayanan rawat inap pada Kuadran I. Posisi ini menunjukkan bahwa rumah sakit memiliki kekuatan internal yang besar dan peluang eksternal yang tinggi. Kesimpulan : Strategi yang direkomendasikan adalah strategi agresif (SO), meliputi peningkatan kualitas pelayanan, pengembangan layanan unggulan, optimalisasi digitalisasi, peningkatan kompetensi SDM, dan modernisasi fasilitas kesehatan untuk meningkatkan mutu pelayanan serta daya saing rumah sakit. Kata Kunci : SWOT, IFAS, EFAS, Strategi Pengembangan, Rawat Inap.